2022
DOI: 10.3389/fimmu.2022.910705
|View full text |Cite
|
Sign up to set email alerts
|

SMRT and NCoR1 fine-tune inflammatory versus tolerogenic balance in dendritic cells by differentially regulating STAT3 signaling

Abstract: Dendritic cell (DC) fine-tunes inflammatory versus tolerogenic responses to protect from immune-pathology. However, the role of co-regulators in maintaining this balance is unexplored. NCoR1-mediated repression of DC immune-tolerance has been recently reported. Here we found that depletion of NCoR1 paralog SMRT (NCoR2) enhanced cDC1 activation and expression of IL-6, IL-12 and IL-23 while concomitantly decreasing IL-10 expression/secretion. Consequently, co-cultured CD4+ and CD8+ T-cells depicted enhanced Th1/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Literature-based interactomes have a bias for prioritizing better studied proteins which can also affect our observations. Nonetheless, a number of macrophage studies 64,65,99,100,105 have pointed towards the major roles of these TFs in immunosuppressive macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature-based interactomes have a bias for prioritizing better studied proteins which can also affect our observations. Nonetheless, a number of macrophage studies 64,65,99,100,105 have pointed towards the major roles of these TFs in immunosuppressive macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…These included phosphoresidues of the CCR1 chemokine receptor, which was previously shown to promote M2 macrophage polarization 63 (FDR < 7.07×10 -3 and Log 2 FC > 2.13). In addition, the NCOR2 TF, which is able to suppress inflammation, showed higher phosphorylation in the M2 states 64,65 (S149 and S152: FDR < 4.78×10 -3 and Log 2 FC > 2.12). In the M2a state, MAFB and HSF1 TFs, whose elevated expression in TAMs associates with more aggressive tumor growth 66,67 , had significantly upregulated phosphosites (MAFB S70: FDR < 2.39×10 -3 and Log 2 FC > 2.71; HSF1 S292: FDR < 3.45×10 -3 and Log 2 FC > 2.27).…”
Section: Several Regulatory Proteins Which Are Expressed In Tams and ...mentioning
confidence: 99%
“…Using multi-omics dimensional analysis, we found that only Stat1 and Stat3 expression was remarkably altered in the four omics. Fas regulates the balance between Stat1 and Stat3 by binding and isolating Stat1 [ 62 ] and contributes to the inflammatory response by promoting T-cell differentiation through Stat3 [ 70 ]. Thus, this phenomenon may be related to the altered functional status of Fas, a downstream molecule that counter-regulates Stat1, thereby increasing the multi-omics activity of Stat3 and contributing to the development of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the non-canonical NF-κB signaling pathway may be more effective in stimulating peripheral tolerance than the canonical NF-κB signaling pathway, which primarily responds to pro-inflammatory signals, and the non-canonical NF-κB pathway in tolDCs may treat inflammatory diseases ( 84 ). Inhibition of core transcription factor pathways such as NF-κB produces tolDCs, which further interfere with NF-κB signaling by increasing IL-10 ( 76 , 85 ). The tolDCs phenotype is promoted by NF-κB p50, which negatively affects the survival of DCs and their ability to effectively activate T cells ( 75 ).…”
Section: Toldcs and Tlr4/irak4/nf-κb Signaling Pathwaymentioning
confidence: 99%